(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Economic Imperatives for Women’s Writing in Early Modern Europe / edited by Carme Font Paz and Nina Geerdink. – Boston: Brill, 2018, Series Women Writers in History, Vol 2, 262 pp., ISBN 978-90-04-38299-2 (hb), ISBN 978-90-04-38302-9 (e-book)